UTILIZATION OF RUBBER SANDALS WASTE AS PARTIAL SUBSTITUTION MATERIAL FOR COARSE AGGREGATE IN CONCRETE MIXTURE - PANDU ARIFIN; SAHAT MARTUA SIHOMBING; ACHMAD PAHRUL RODJI (CV KULTURA DIGITAL MEDIA, 2024)
In Indonesia, there is an increasing demand for building materials, especially concrete which is popularly used to construct bridges, houses, buildings, and highways because it is cheap and easy to form. However, concrete has weaknesses in resisting tensile loads and the repeated use of aggregates leads to a reduction in natural resources. This study investigates the use of waste rubber sandals as an alternative to coarse gravel in concrete to reduce environmental damage and add economic value to construction projects through experimental concrete strength testing. From the data analysis and discussion in the previous chapter regarding the use of rubber sandal waste with variations of 0%, 5%, and 10%, the results of compressive strength testing on normal concrete at the age of 28 days were 440 kN (f'c 24.91 MPa), while in variation 1 rubber sandal waste 5% was 297 kN (f'c 16.82 MPa) and in variation 2 rubber sandal waste 10% was 248 kN (f'c 14.04 MPa).